Chemical constituents of the lichen Dermatocarpon luridum and pKa value of isolated mycosporine - Thu Tram, Nguyen Thi; Tuan, Nguyen Trong; Marylène, Chollet-Krugler; Solenn, Ferron; Joël, Boustie (Vietnam Journal of Chemistry, 2017)
A phytochemical study on the lichen Dermatocarpon luridum led to the isolation of four known compounds, including mycosporine glutaminol (1), 2-amino-3-acetylaminopropionic acid (2), (22E,24R)-ergosta-7,22-diene-3b,5a,6b-triol (3) and (2S,3S,4R,2’R)-2-(2’-hydroxytetracosanoylamino)octadecan-1,3,4-triol (4). Their structures were determined by extensive spectroscopic analyses including UV, IR, ESI-HRMS, 1D, 2D NMR and specific rotation as well as by comparison of the data with those in the literature. The pKa value in an aqueous solution of (1) was determined by UV-VIS spectrophotometry at 298 K. With the low pKa value 1.29, only the neutral form of (1) was present and responsible for the UV absorption in water at pH 7. Keywords. Dermatocarpon, mycosporine, lichen, pKa.